Pengaruh Beban Kerja terhadap Subjective Well Being Ustadz dan Ustadzah Muda - Yuva Monica Sari; Any Nurhayaty; Tansri Adzlan Syah (Universitas Muhammadiyah Metro, 2025)
This study examines the influence of workload on subjective well-being among young ustadz and ustadzah working in Islamic boarding schools (pesantren). Using a quantitative approach with simple linear regression analysis, this research involved 276 respondents aged 18–29 years who were actively teaching in various pesantren across Indonesia. Data were collected using validated measurement instruments, including the Satisfaction With Life Scale (SWLS), the Positive and Negative Affect Schedule (PANAS) based on Diener’s theory (2018), and a workload scale developed based on Gawron’s theory (2018). Data analysis was conducted using SPSS version 27, encompassing validity testing, reliability testing, normality testing, and Pearson product–moment correlation analysis. The results indicated that workload had a positive and significant relationship with subjective well-being (r = 0.520, p < 0.001). This finding suggests that higher workload is associated with higher levels of subjective well-being when work is perceived as meaningful and interpreted as a form of devotion. Within the pesantren context, spiritual meaning and religious values play a crucial role in transforming work pressure into a source of psychological satisfaction and happiness. These results highlight the importance of value-based work environments in shaping positive psychological outcomes. This study contributes to the development of positive psychology, particularly in enhancing the understanding of well-being within religious-based work settings.